2004
DOI: 10.1074/jbc.m407062200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sensors of the Regulatory Switch on the Regulatory Light Chain of Smooth Muscle Myosin

Abstract: Here we used three different approaches to test this notion, which are reactivity of cysteine thiols, pyrene and acrylodan spectral analysis, and pyrene fluorescence quenching. All methods detected significant differences between the unphosphorylated and phosphorylated regulatory light chain N termini in heavy meromyosin, a double-headed subfragment with an intact regulatory switch. These differences were not observed for subfragment-1, a single-headed, unregulated subfragment. In the presence of either ATP or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
21
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 60 publications
(60 reference statements)
5
21
0
Order By: Relevance
“…Studies with calcium-regulated scallop HMM show similar trends induced by calcium binding (12). The two RLC can be cross-linked in the unphosphorylated, but not phosphorylated smooth HMM (13), and phosphorylation causes a large structural rearrangement of the RLC Nterminus (14) to a more exposed and nonpolar environment (15) consistent with recent EPR studies (16). Cryo-EM image reconstructions of nucleotide-bound smooth HMM ordered on a lipid monolayer have visualized contacts between the two CDs that are abolished upon phosphorylation (17,18).…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Studies with calcium-regulated scallop HMM show similar trends induced by calcium binding (12). The two RLC can be cross-linked in the unphosphorylated, but not phosphorylated smooth HMM (13), and phosphorylation causes a large structural rearrangement of the RLC Nterminus (14) to a more exposed and nonpolar environment (15) consistent with recent EPR studies (16). Cryo-EM image reconstructions of nucleotide-bound smooth HMM ordered on a lipid monolayer have visualized contacts between the two CDs that are abolished upon phosphorylation (17,18).…”
supporting
confidence: 74%
“…But it is clear that nucleotide at the active site biases the structure more toward an OFF state. Mazhari et al (15) showed that the environment of the RLC N-terminus (phosphorylated or not) in the absence of nucleotides was intermediate between the nucleotide bound unphosphorylated and phosphorylated states in HMM. The fact that we see little effect of phosphorylation on the dynamics in the absence of nucleotides is consistent with the general trend of the Mazhari et al data (15).…”
Section: Structural Models Of Heavy Meromyosin: Implications Of Dynammentioning
confidence: 99%
See 2 more Smart Citations
“…27) versus HMM (used here), and (iii) a large structural transition in the N-terminal domain from disordered to ordered helix was found in HMM (without ATP), but not in S1 (27). Yet another study has shown that fluorophores on the RLC N-terminal domain sense changes in solvent exposure upon ATP binding and phosphorylation but only in regulated constructs HMM but not S1 (29). Therefore it is likely that backbone conformational heterogeneity in the N-terminal domain contributes to the heterogeneity in the RLC-RLC distances, consistent with the variation of the distance distribution widths measured here.…”
Section: Discussionmentioning
confidence: 82%